ANALISIS STRATEGI PENGEMBANGAN OBJEK WISATA ALAM AIR TERJUN LUBUK HITAM KECAMATAN BUNGUS TELUK KABUNG - Riri Rahmania; Dedi Hermon (JURNAL BUANA, 2021)
The purpose of this research is (1) Analyzing the potential that can be developed in Lubuk Hitam Waterfall tourism object. (2) Formulate a strategy analysis for the development of a tourist attraction in Lubuk Hitam Waterfall based on its potential. (3) Formulate priority factors that can be developed at the Lubuk Hitam Waterfall tourist attraction based on the selected solution strategy for developedment and sustainability. The research method used is Mixed Methods using the SWOT Analysis Technique and Analysis Hierarchy Proses (AHP). The data for this study were collected through observation, interviews and questionnaires. The parties who became respondents in this study were tourists, the community and the Tourism Awareness Youth (Pokdarwis). The result show (1) Lubuk Hitam Waterfall Tourism Object has various potentials for the development of tourist objects, (2) Based on a SWOT analysis, Lubuk Hitam Waterfall tourism object is included in the rapid growth strategy, (3) AHP process results The alternative priority strategy chosen is “Improving the performance of tourism managers by utilizing the role of the government for more optimal management of the Lubuk Hitam Waterfall Tourism Object”.